Hardening composition and joint structure using same
The curable composition with specific components ensures strong adhesion and long-lasting rubber elasticity, addressing adhesion issues and water leakage in building structures.
Patent Information
- Application Number
- JP2021061370
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-31
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Conventional curable compositions exhibit poor adhesion to ceramic plate exterior wall members and lose rubber elasticity over time, leading to separation and water leakage due to changes in joint width caused by temperature, vibration, or external forces.
A curable composition comprising an organic polymer with hydrolyzable silyl groups, an amine compound with a melting point of 55°C or higher, an aminosilane compound, and a silanol condensation catalyst, which includes polyalkylene oxide and acrylic polymer to enhance adhesion and maintain rubber elasticity.
The composition maintains excellent adhesive properties and rubber elasticity for a long period, preventing separation and water leakage by adapting to joint width changes.
Smart Images

Figure 0007603979000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable composition that is cured by moisture in the atmosphere (air) to produce a cured product that has excellent weather resistance and adhesiveness. [Background technology]
[0002] Conventionally, a curable composition containing an oxyalkylene polymer having a crosslinkable hydrolyzable silyl group has been known (for example, Patent Document 1). The curable composition produces a cured product having excellent adhesiveness by hydrolysis of the crosslinkable hydrolyzable silyl group due to moisture contained in the atmosphere, followed by dehydration condensation.
[0003] As a curable composition, Patent Document 2 discloses a moisture-curable composition containing an alkoxysilyl group-containing polyoxyalkylene polymer, an organic carboxylate, and an organic amine.
[0004] Such curable compositions are used, for example, in the exterior walls of architectural structures, by filling the joints (so-called "joints") between exterior wall members such as mortar boards, concrete boards, ALC (Autoclaved Light-weight Concrete) boards, metal boards, etc. By using the curable composition in this way, it is possible to prevent rainwater from penetrating into the interior of the architectural structure through the joints between the exterior wall members.
[0005] In the exterior walls of building structures, the joint width changes slightly as exterior wall components expand or contract with temperature changes, and as exterior wall components move due to vibrations caused by earthquakes or strong winds or external forces. Therefore, it is necessary for the curable composition to have excellent rubber elasticity after curing and be expandable and contractible so that it can firmly adhere to the exterior wall and follow changes in the joint width. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5698422 [Patent Document 2] Japanese Patent Application Publication No. 6-16922 Summary of the Invention [Problem to be solved by the invention]
[0007] However, recently, ceramic panels have become popular as exterior wall components because of their design, but conventional curable compositions have a problem of low adhesiveness to such exterior wall components. Therefore, when the joint width changes, it is difficult for the cured product of the curable composition to expand and contract in response to the change in the joint width. In such cases, peeling occurs at the adhesive interface and the exterior wall components are damaged, causing problems such as rainwater penetrating into the building structure and causing water leakage. Therefore, there is a need to improve the adhesiveness of the curable composition.
[0008] Furthermore, with conventional curable compositions, after curing, the rubber elasticity decreases over time and the composition becomes hard, making it difficult for the composition to expand and contract in response to changes in the joint width when such changes occur. This can lead to peeling at the adhesive interface, allowing rainwater to penetrate into building structures and cause water leaks.
[0009] Therefore, an object of the present invention is to provide a curable composition that has excellent adhesive properties and can maintain excellent rubber elasticity for a long period of time after curing, and a joint structure using the same. [Means for solving the problem]
[0010] The curable composition of the present invention is characterized by containing an organic polymer (I) having a hydrolyzable silyl group, an amine compound (C) having a melting point of 55°C or higher, an aminosilane compound (D), and a silanol condensation catalyst (E).
[0011] [Organic polymer having hydrolyzable silyl group (I)] The curable composition of the present invention contains an organic polymer (I) having a hydrolyzable silyl group. The organic polymer (I) having a hydrolyzable silyl group makes it possible to provide a moisture-curable composition that can be cured by moisture in the atmosphere.
[0012] (Polyalkylene oxide (A)) The organic polymer (I) having a hydrolyzable silyl group preferably contains a polyalkylene oxide (A) having a hydrolyzable silyl group, which can improve the adhesiveness of the curable composition.
[0013] The polyalkylene oxide (A) has a hydrolyzable silyl group.
[0014] The hydrolyzable silyl group is a group in which 1 to 3 hydrolyzable groups are bonded to a silicon atom. The hydrolyzable group of the hydrolyzable silyl group is not particularly limited, and examples thereof include a hydrogen atom, a halogen atom, an alkoxy group, an acyloxy group, a ketoximate group, an amino group, an amide group, an acid amide group, an aminooxy group, a mercapto group, and an alkenyloxy group.
[0015] The hydrolyzable silyl group of the polyalkylene oxide (A) is preferably an alkoxysilyl group because the hydrolysis reaction is mild. Examples of the alkoxysilyl group include trialkoxysilyl groups such as trimethoxysilyl group, triethoxysilyl group, triisopropoxysilyl group, and triphenoxysilyl group; dialkoxysilyl groups such as methyldimethoxysilyl group and methyldiethoxysilyl group; and monoalkoxysilyl groups such as dimethylmethoxysilyl group and dimethylethoxysilyl group. Among them, dialkoxysilyl groups are more preferred, and methyldimethoxysilyl group is particularly preferred. The polyalkylene oxide (A) having a dialkoxysilyl group can provide a curable composition that exhibits excellent rubber elasticity and adhesiveness after curing.
[0016] The polyalkylene oxide (A) preferably has 1 to 2 hydrolyzable silyl groups on average per molecule. When the polyalkylene oxide (A) has 1 or more hydrolyzable silyl groups, the curability of the curable composition is improved. When the polyalkylene oxide (A) has 2 or less hydrolyzable silyl groups, the mechanical strength or elongation of the cured product of the curable composition is improved. Furthermore, the polyalkylene oxide (A) preferably has a hydrolyzable silyl group at least on one of both ends of the molecular chain.
[0017] The average number of hydrolyzable silyl groups per molecule in the polyalkylene oxide (A) is 1 It can be calculated based on the concentration of hydrolyzable silyl groups in the polyalkylene oxide (A) determined by H-NMR and the number average molecular weight of the polyalkylene oxide (A) determined by GPC.
[0018] The polyalkylene oxide (A) has a main chain represented by the general formula: -(RO) n - (wherein R represents an alkylene group having 1 to 14 carbon atoms, and n represents the number of repeating units and is a positive integer) is preferred. The main chain skeleton of the polyalkylene oxide may be composed of only one type of repeating unit, or may be composed of two or more types of repeating units.
[0019] Examples of the main chain skeleton of the polyalkylene oxide (A) include polyethylene oxide, polypropylene oxide, polybutylene oxide, polytetramethylene oxide, polyethylene oxide-polypropylene oxide copolymer, and polypropylene oxide-polybutylene oxide copolymer. Among them, polypropylene oxide is preferable. Polypropylene oxide can provide a curable composition that exhibits excellent rubber elasticity and adhesiveness after curing.
[0020] The number average molecular weight of the polyalkylene oxide (A) is preferably 20,000 to 50,000, more preferably 20,000 to 40,000. When the number average molecular weight of the polyalkylene oxide (A) is 20,000 or more, the rubber elasticity of the cured product of the curable composition is improved. When the number average molecular weight of the polyalkylene oxide (A) is 50,000 or less, the coatability of the curable composition is improved.
[0021] The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polyalkylene oxide (A) is preferably 1.5 or less, more preferably 1.3 or less, more preferably from 1.0 to 1.3, and particularly preferably from 1.0 to 1.2. The polyalkylene oxide having a molecular weight distribution of 1.5 or less improves the rubber elasticity of the cured product of the curable composition.
[0022] In the present invention, the number average molecular weight and weight average molecular weight of the polyalkylene oxide refer to values calculated in terms of polystyrene measured by GPC (gel permeation chromatography).
[0023] Specifically, 6 to 7 mg of polyalkylene oxide is collected and the collected polyalkylene oxide is supplied to a test tube. An ortho-dichlorobenzene (o-DCB) solution containing 0.05% by mass of dibutylhydroxytoluene (BHT) is prepared, and this solution is added to a test tube and diluted to a polyalkylene oxide concentration of 1 mg / mL to prepare a diluted solution. The diluted solution is shaken using a dissolution and filtration device at 145°C and a rotation speed of 25 rpm for 1 hour to dissolve the polyalkylene oxide in the solution, thereby preparing a measurement sample. Using this measurement sample, the number average molecular weight and weight average molecular weight of the polyalkylene oxide can be measured by the GPC method.
[0024] The number average molecular weight and weight average molecular weight of the polyalkylene oxide can be measured, for example, using the following measuring device and under the following measuring conditions. Measuring device: TOSOH product name "HLC-8121GPC / HT" Measurement conditions Column: TSKgelGMHHR-H(20)HT x 3 TSKguardcolumn-HHR(30)HT x 1 Mobile phase: o-DCB 1.0mL / min Sample concentration: 1mg / mL Detector: Bryce type refractometer Standard material: Polystyrene (TOSOH, molecular weight: 500-8420000) Elution conditions: 145℃ SEC temperature: 145℃
[0025] The polyalkylene oxide (A) containing a hydrolyzable silyl group can be a commercially available product. For example, examples of polyalkylene oxides having a main chain skeleton of polypropylene oxide and a methyldimethoxysilyl group include those manufactured by AGC Inc. under the product names "Exestar S4530", "Exestar S6735", and "Exestar SAX720".
[0026] (Acrylic polymer (B)) The organic polymer (I) having a hydrolyzable silyl group preferably further contains an acrylic polymer (B) having a hydrolyzable silyl group. The acrylic polymer (B) can improve the adhesiveness of the curable composition. Furthermore, the weather resistance of the curable composition after curing can be improved by using the acrylic polymer (B) in combination with the above-mentioned polyalkylene oxide (A).
[0027] The hydrolyzable silyl group of the acrylic polymer (B) is preferably an alkoxysilyl group, since the cured product of the curable composition can maintain excellent rubber elasticity for a long period of time. Examples of the alkoxysilyl group include trialkoxysilyl groups such as trimethoxysilyl group, triethoxysilyl group, triisopropoxysilyl group, and triphenoxysilyl group; dialkoxysilyl groups such as methyldimethoxysilyl group and methyldiethoxysilyl group; and monoalkoxysilyl groups such as dimethylmethoxysilyl group and dimethylethoxysilyl group. Among them, trialkoxysilyl group is more preferred, and trimethoxysilyl group is particularly preferred.
[0028] The main chain skeleton of the acrylic polymer (B) is preferably a polymer of an acrylic monomer. The acrylic monomer has an ethylenically unsaturated double bond, and the acrylic monomer is subjected to addition polymerization at the ethylenically unsaturated double bond to obtain a polymer of the acrylic monomer.
[0029] Examples of the acrylic monomer in the acrylic polymer (B) include acrylic acid, methacrylic acid, and alkyl (meth)acrylate. Among them, alkyl (meth)acrylate is preferred. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, and lauryl (meth)methacrylate. These alkyl (meth)acrylates may be used alone or in combination of two or more. The term "(meth)acrylate" refers to methacrylate and / or acrylate.
[0030] The main chain skeleton of the acrylic polymer (B) is preferably a copolymer of a monomer containing methyl (meth)acrylate and butyl (meth)acrylate, more preferably a copolymer of a monomer containing methyl methacrylate and butyl acrylate. The acrylic polymer (B) having a main chain skeleton composed of the copolymer can improve the tensile shear adhesive strength of the curable composition after curing.
[0031] In the acrylic polymer (B), the monomers used in the polymer constituting the main chain may further contain other monomers in addition to the acrylic monomer. Examples of other monomers include styrene derivatives such as styrene, indene, α-methylstyrene, p-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, p-methoxystyrene, p-tert-butoxystyrene, and divinylbenzene; compounds having a vinyl ester group such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl benzoate, and vinyl cinnamate; maleic anhydride, N-vinylpyrrolidone, N-vinylmorpholine, (meth)acrylonitrile, (meth)acrylamide, N-cyclohexylmaleimide, N-phenylmaleimide, N-laurylmaleimide, N-benzylmaleimide, n-propyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, tert-amyl vinyl ether, cyclohexyl vinyl ether, 2-ethylhexyl vinyl ether, dodecyl vinyl ether, octadecyl vinyl ether, 2-chloroethyl vinyl ether, ethylene glycol butyl vinyl ether, and triethylene glycol butyl vinyl ether. Examples of vinyloxy groups include methyl vinyl ether, benzoate (4-vinyloxy)butyl, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, butane-1,4-diol-divinyl ether, hexane-1,6-diol-divinyl ether, cyclohexane-1,4-dimethanol-divinyl ether, di(4-vinyloxy)butyl isophthalate, di(4-vinyloxy)butyl glutarate, di(4-vinyloxy)butyl succinate, trimethylolpropane trivinyl ether, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, 6-hydroxyhexyl vinyl ether, cyclohexane-1,4-dimethanol monovinyl ether, diethylene glycol monovinyl ether, 3-aminopropyl vinyl ether, 2-(N,N-diethylamino)ethyl vinyl ether, urethane vinyl ether, and polyester vinyl ether.These monomers may be used alone or in combination of two or more.
[0032] The polymerization method for the acrylic polymer (B) is not particularly limited, and any known method can be used. Examples of the polymerization methods include free radical polymerization, anionic polymerization, cationic polymerization, UV radical polymerization, living anionic polymerization, living cationic polymerization, and living radical polymerization.
[0033] The weight average molecular weight of the acrylic polymer (B) is preferably 2,000 to 50,000, more preferably 3,000 to 20,000. When the weight average molecular weight of the acrylic polymer (B) is 2,000 or more, it is possible to provide a curable composition that reduces thermal deterioration after curing and can maintain excellent rubber elasticity for a longer period of time. When the weight average molecular weight of the acrylic polymer (B) is 50,000 or less, it is possible to ensure excellent thread breakage properties of the curable composition, and thus the curable composition can be applied satisfactorily.
[0034] The weight average molecular weight of the acrylic polymer (B) is a value measured in terms of polystyrene by GPC (gel permeation chromatography). The specific measurement method and conditions are the same as those for the measurement of the weight average molecular weight of the polyalkylene oxide described above.
[0035] The content of the acrylic polymer (B) in the curable composition is preferably 10 to 200 parts by mass, more preferably 20 to 150 parts by mass, and particularly preferably 30 to 100 parts by mass, relative to 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the acrylic polymer (B) is 10 parts by mass or more, the photodegradation of the cured product of the curable composition can be reduced, and the durability can be improved. When the content of the acrylic polymer (B) is 200 parts by mass or less, the extensibility of the cured product of the curable composition can be improved. This improves the followability of the cured product to changes in joint width.
[0036] [Amine compounds (C)] The curable composition contains an amine compound (C) having a melting point of 55° C. or higher. The amine compound (C) can provide a curable composition that can maintain excellent rubber elasticity for a long period of time after curing.
[0037] The melting point of the amine compound is 55°C or higher, preferably 58°C or higher, more preferably 58 to 100°C, and particularly preferably 58 to 90°C.
[0038] In the present invention, the melting point of the amine compound refers to a temperature measured by differential scanning calorimetry (DSC) in accordance with JIS K7121 (1987). Specifically, the amine compound is heated from 10°C to 150°C at a heating rate of 5°C / min using a differential scanning calorimeter (e.g., Shimadzu Corporation's DSC-60), and the melting peak temperature of the DSC curve during this heating process is taken as the melting point of the amine compound. In addition, when there are multiple melting peaks, the temperature at the apex of the melting peak with the greatest heat absorption is taken as the melting point.
[0039] In the present invention, the amine compound (C) means a compound having at least one amino group (-NH2) in one molecule. In the amine compound (C), the hydrogen atom of the amino group may be substituted with an organic group such as an alkyl group or an aryl group. It is preferable that the amine compound (C) does not have a hydrolyzable silyl group. It is also preferable that the amine compound (C) does not contain a silicon atom.
[0040] Examples of the amine compound (C) include monoamine compounds, diamine compounds, and triamine compounds. Among these, monoamine compounds and diamine compounds are preferred, and diamine compounds are more preferred.
[0041] Preferred examples of the amine compound (C) include a monoamine compound represented by the following formula (1), a diamine compound represented by the following formula (2), and a diamine compound represented by the following formula (3). Among these, the diamine compound represented by the following formula (2) and the diamine compound represented by the following formula (3) are preferred, and the diamine compound represented by the following formula (2) is more preferred. R 1 -NH2(1) R 2 -NH-R 3 -NH2(2) NH2-R 4 -NH2(3) (In formula (1), R 1 is a linear or branched alkyl group, a monovalent saturated alicyclic hydrocarbon group, or an aryl group. 2 is a linear or branched alkyl group, a monovalent saturated alicyclic hydrocarbon group, or an aryl group; R 3 is an alkylene group. 4 is an alkylene group.
[0042] In the monoamine compound represented by formula (1), R 1 The number of carbon atoms in R is preferably 15 to 35, more preferably 15 to 30, and still more preferably 15 to 25. 1 By setting the number of carbon atoms in the above range, it is possible to provide a curable composition that can maintain excellent rubber elasticity for a long period of time after curing. 1 As the alkyl group, a straight-chain or branched-chain alkyl group is preferable.
[0043] In the diamine compound represented by formula (2), R 2 and R 3 The total number of carbon atoms in R is preferably 15 to 40, more preferably 15 to 30, and particularly preferably 15 to 25. 2 and R 3 By setting the total number of carbon atoms in the above range, it is possible to provide a curable composition that can maintain excellent rubber elasticity for a long period of time after curing. 2As the alkyl group, a straight-chain or branched-chain alkyl group is preferable.
[0044] In the diamine compound represented by formula (3), R 4 The number of carbon atoms in R is preferably 10 to 40, more preferably 15 to 40, still more preferably 15 to 30, and particularly preferably 15 to 25. 4 By setting the number of carbon atoms within the above range, it is possible to provide a curable composition that can maintain excellent rubber elasticity for a longer period of time after curing.
[0045] As the amine compound (C), specifically, behenylamine (C 22 H 45 -NH2, melting point 63℃), behenyl propylene diamine (C 22 H 45 -NH-C3H6-NH2, melting point 60℃), 1,10-diaminodecane (NH2-C 10 H 20 -NH2, melting point 62℃), 1,12-diaminododecane (NH2-C 12 H 24 -NH2, melting point 70℃), dioctadecylamine ((C 18 H 37 ) 2-NH, melting point 72°C), and 1-tetratriacontanamine (C 34 H 69 --NH2, melting point 84°C). Among them, behenylpropylenediamine, 1,10-diaminodecane, and 1,12-diaminododecane are preferred, and behenylpropylenediamine is more preferred. The amine compound (C) may be used alone or in combination of two or more kinds.
[0046] The content of the amine compound (C) in the curable composition is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the amine compound (C) is 0.1 parts by mass or more, a curable composition capable of maintaining excellent rubber elasticity for a long period of time after curing can be provided. When the content of the amine compound (C) is 10 parts by mass or less, the curability of the curable composition is improved.
[0047] [Aminosilane compound (D)] The curable composition contains an aminosilane compound (D). The aminosilane compound (D) is preferably an aminoalkoxysilane. The aminosilane compound (D) is preferably an alkoxysilane oligomer, which is a hydrolysis condensate of an alkoxysilane containing an aminoalkoxysilane. The aminosilane compound (D) contains a silicon atom. The aminosilane compound (D) may be used alone or in combination of two or more kinds.
[0048] (Aminoalkoxysilane) Aminoalkoxysilane refers to a compound having at least one amino group-containing functional group and at least two alkoxy groups directly bonded to silicon atom in one molecule.The amino group-containing functional group is preferably directly bonded to silicon atom.The aminoalkoxysilane is preferably a compound having one amino group-containing functional group and three alkoxy groups directly bonded to silicon atom in one molecule.
[0049] As the amino group-containing functional group, an aminopropyl functional group is preferred because it improves the adhesiveness of the curable composition. Examples of the aminopropyl functional group include -(CH2)3-NH2 and -(CH2)3-NHR 5At least one aminopropyl functional group selected from the group consisting of -(CH2)3-NH(CH2)2-NH2 (3-[N-(2-aminoethyl)amino]propyl group) and -(CH2)3-NH(CH2)2-NH2-NH2 (3-[[2-(2-aminoethylamino)ethyl]amino]propyl group) is preferred. As the aminopropyl functional group, -(CH2)3-NH2 and -(CH2)3-NH(CH2)2-NH2 are more preferred.
[0050] -(CH2)3-NHR 5 In R 5 is an alkyl group having 1 to 18 carbon atoms, a monovalent saturated alicyclic hydrocarbon group having 3 to 18 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
[0051] R 5 In the above, examples of the alkyl group having 1 to 18 carbon atoms include linear alkyl groups and branched alkyl groups. Examples of linear alkyl groups include methyl, ethyl, propyl, n-butyl, n-pentyl, n-hexyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, and n-octadecyl groups. Examples of linear alkyl groups include methyl, ethyl, and n-butyl groups. Examples of branched alkyl groups include isopropyl, isobutyl, sec-butyl, and tert-butyl groups.
[0052] R 5 In the above formula, examples of the monovalent saturated alicyclic hydrocarbon group having 3 to 18 carbon atoms include a cyclopentyl group, a cycloheptyl group, a cyclohexyl group, a 4-methylcyclohexyl group, and a cyclooctyl group, with a cyclohexyl group being preferred.
[0053] R 5 In the above formula, examples of the aryl group having 6 to 12 carbon atoms include a phenyl group and a benzyl group, and a phenyl group is preferable.
[0054] Specific examples of aminoalkoxysilanes include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-methylaminopropyltrimethoxysilane, N-methylaminopropyltriethoxysilane, Nn-butylaminopropyltrimethoxysilane, Nn-butylaminopropyltriethoxysilane, N-cyclohexylaminopropyltrimethoxysilane, N-cyclohexylaminopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, and N-phenylaminopropyltriethoxysilane. Propyltriethoxysilane, 3-[N-(2-aminoethyl)amino]propyltrimethoxysilane, 3-[N-(2-aminoethyl)amino]propyltriethoxysilane, [3-[2-(2-aminoethylamino)ethylamino]propyl]trimethoxysilane, [3-[2-(2-aminoethylamino)ethylamino]propyl]triethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-methyl-aminopropylmethyldimethoxysilane, N-methyl-aminopropyl N-butyl-aminopropyl methyldimethoxysilane, N-butyl-aminopropyl methyldiethoxysilane, N-cyclohexylaminopropyl methyldimethoxysilane, N-cyclohexylaminopropyl methyldiethoxysilane, N-phenyl-aminopropyl methyldimethoxysilane, N-phenyl-aminopropyl methyldiethoxysilane, 3-[N-(2-aminoethyl)amino]propyl methyldimethoxysilane, 3-[N-(2-aminoethyl)amino]propyl methyldiethoxysilane silane, [3-[2-(2-aminoethylamino)ethylamino]propyl]methyldimethoxysilane, [3-[2-(2-aminoethylamino)ethylamino]propyl]methyldiethoxysilane, N,N'-bis-[3-(trimethoxysilyl)propyl]ethylenediamine, N,N'-bis-[3-(triethoxysilyl)propyl]ethylenediamine, N,N'-bis-[3-(methyldimethoxysilyl)propyl]ethylenediamine, N,N'-bis-[3-(trimethoxysilyl)propyl]hexamethylenediamine, and N,Examples of the aminoalkoxysilane include 3-aminopropyltriethoxysilane, 3-[N-(2-aminoethyl)amino]propyltrimethoxysilane, and 3-[N-(2-aminoethyl)amino]propyltriethoxysilane, and more preferably 3-[N-(2-aminoethyl)amino]propyltriethoxysilane.
[0055] (Alkoxysilane Oligomer) In addition, the aminosilane compound (D) may be an alkoxysilane oligomer, which is a hydrolysis condensate of an alkoxysilane containing an aminoalkoxysilane. That is, the curable composition preferably contains, as the aminosilane compound (D), an alkoxysilane oligomer obtained by hydrolyzing an alkoxysilane containing an aminoalkoxysilane and then condensing it. Note that the aminoalkoxysilane in the alkoxysilane oligomer is the same as the aminoalkoxysilane described above, so a detailed description is omitted here. The aminoalkoxysilane in the alkoxysilane oligomer may be used alone or in combination of two or more kinds.
[0056] As the aminoalkoxysilane in the alkoxysilane oligomer, 3-[N-(2-aminoethyl)amino]propyltrimethoxysilane and 3-[N-(2-aminoethyl)amino]propyltriethoxysilane are preferred, and 3-[N-(2-aminoethyl)amino]propyltriethoxysilane is more preferred.
[0057] In the alkoxysilane oligomer, the alkoxysilane preferably further contains an alkylalkoxysilane in addition to the aminoalkoxysilane. That is, the aminosilane compound (D) is preferably an alkoxysilane oligomer which is a hydrolysis condensation product of an alkoxysilane including an aminoalkoxysilane and an alkylalkoxysilane. The curable composition preferably contains, as the aminosilane compound (D), an alkoxysilane oligomer obtained by hydrolyzing and then condensing an alkoxysilane including an aminoalkoxysilane and an alkylalkoxysilane.
[0058] Alkylalkoxysilane means a compound in which at least one alkyl group and at least two alkoxy groups are directly bonded to a silicon atom. Examples of alkylalkoxysilane include monoalkyltrialkoxysilane in which one alkyl group and three alkoxy groups are directly bonded to a silicon atom, and dialkyldialkoxysilane in which two alkyl groups and two alkoxy groups are directly bonded to a silicon atom. Specific examples of monoalkyltrialkoxysilane include methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, and hexyltrimethoxysilane. Specific examples of dialkyldialkoxysilane include dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, and diethyldiethoxysilane. Among them, monoalkyltrialkoxysilane is preferred, and ethyltriethoxysilane is more preferred. The alkylalkoxysilane may be used alone or in combination of two or more.
[0059] The alkoxysilane oligomer is preferably an alkoxysilane oligomer (d1) which is a hydrolysis condensate of aminoalkoxysilane. That is, the alkoxysilane oligomer (d1) which is obtained by hydrolyzing and then condensing an alkoxysilane containing only aminoalkoxysilane is preferably mentioned. The alkoxysilane oligomer (d1) is preferably a hydrolysis condensate of 3-[N-(2-aminoethyl)amino]propyltrialkoxysilane and a hydrolysis condensate of 3-aminopropyltrialkoxysilane, and more preferably a hydrolysis condensate of 3-[N-(2-aminoethyl)amino]propyltrialkoxysilane.
[0060] As the alkoxysilane oligomer, there can be preferably mentioned an alkoxysilane oligomer (d2) which is a hydrolysis condensate of an alkylalkoxysilane and an aminoalkoxysilane.
[0061] The alkoxysilane oligomer (d2) is preferably a hydrolysis condensate of monoalkyltrialkoxysilane and aminoalkoxysilane having one aminopropyl functional group and three alkoxy groups directly bonded to silicon atom. That is, the alkoxysilane oligomer (d2) is preferably an alkoxysilane oligomer obtained by hydrolyzing and then condensing an alkoxysilane containing monoalkyltrialkoxysilane and aminoalkoxysilane having one aminopropyl functional group and three alkoxy groups directly bonded to silicon atom. Among them, the hydrolysis condensate of monoalkyltrialkoxysilane and 3-[N-(2-aminoethyl)amino]propyltrialkoxysilane is more preferred, and the hydrolysis condensate of ethyltriethoxysilane and 3-[N-(2-aminoethyl)amino]propyltriethoxysilane is more preferred.
[0062] The alkoxysilane oligomer (d2) is preferably a hydrolysis condensate of a dialkyl dialkoxysilane and an aminoalkoxysilane having one aminopropyl functional group and three alkoxy groups directly bonded to a silicon atom. That is, the alkoxysilane oligomer (d2) is preferably an alkoxysilane oligomer obtained by hydrolyzing and then condensing an alkoxysilane containing a dialkyl dialkoxysilane and an aminoalkoxysilane having one aminopropyl functional group and three alkoxy groups directly bonded to a silicon atom.
[0063] The alkoxysilane oligomer preferably has an aminopropyl functional group. The aminopropyl functional group possessed by the alkoxysilane oligomer is the same as the aminopropyl functional group possessed by the above-mentioned aminoalkoxysilane, and therefore a detailed description thereof will be omitted here.
[0064] The alkoxysilane oligomer may be a commercially available product, such as "Dynasilan 1146" manufactured by Evonik Dexa and "VX225" manufactured by Momentive.
[0065] In the alkoxysilane oligomer, the nitrogen atom content is preferably 1% by mass or more, more preferably 3% by mass or more, and particularly preferably 5% by mass or more. When the nitrogen atom content is 1% by mass or more, a curable composition having excellent adhesiveness and excellent elongation after curing can be provided. The upper limit of the nitrogen atom content is not particularly limited, but is preferably 20% by mass or less, more preferably 10% by mass or less. When the nitrogen atom content is 20% by mass or less, the cured product of the curable composition can maintain excellent rubber elasticity even when the temperature becomes high.
[0066] The nitrogen atom content in the alkoxysilane oligomer is a value measured based on CHN elemental analysis, and can be determined, for example, under the following measurement conditions. ·Equipment: CHN elemental analyzer (vario EL III manufactured by Elementar) Sample size: 10mg Combustion tube temperature: 950℃ · Reduction tube temperature: 500℃ Carrier gas: 200mL / min Detector: TCD Standard sample: Acetanilide (standard sample for elemental analysis) C=71.09%, H=6.710%, N=10.36%) Quantitative method: Multi-point calibration curve method using standard samples
[0067] The aminosilane compound (D) preferably contains at least one of an aminoalkoxysilane and an alkoxysilane oligomer, more preferably contains an alkoxysilane oligomer, and even more preferably contains both an aminoalkoxysilane and an alkoxysilane oligomer.
[0068] The aminosilane compound (D) is preferably in a liquid state under conditions of 25° C. and 0.10 MPa. By using the liquid aminosilane compound (D), the curable composition can exhibit good adhesiveness.
[0069] The viscosity of the aminosilane compound (D) at 20° C. is preferably from 1 to 200 mPa·s, and more preferably from 5 to 100 mPa·s. The viscosity of the aminosilane compound (D) at 20° C. refers to a value measured in accordance with JIS Z8803.
[0070] The content of the aminosilane compound (D) in the curable composition is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the aminosilane compound (D) is 0.1 parts by mass or more, the adhesiveness of the curable composition is improved. When the content of the aminosilane compound (D) is 10 parts by mass or less, the curability of the curable composition is improved.
[0071] [Silanol condensation catalyst (E)] The curable composition contains a silanol condensation catalyst (E), which is a catalyst for promoting a dehydration condensation reaction between silanol groups formed by hydrolysis of a hydrolyzable silyl group contained in the polyalkylene oxide (A) and an alkoxysilyl group contained in the aminosilane compound (D).
[0072] The silanol condensation catalyst (E) is not particularly limited, and examples thereof include organic tin compounds such as dioctyltin monodecanoate, 1,1,3,3-tetrabutyl-1,3-dilauryloxycarbonyl-distannoxane, dibutyltin dilaurate, dibutyltin oxide, dibutyltin diacetate, dibutyltin phthalate, bis(dibutyltin laurate) oxide, dibutyltin bis(acetylacetonate), dibutyltin bis(monoester maleate), tin octoate, dibutyltin octoate, dioctyltin oxide, dibutyltin bis(triethoxysilicate), bis(dibutyltin bistriethoxysilicate) oxide, and dibutyltin oxybisethoxysilicate; organic titanium compounds such as tetra-n-butoxytitanate and tetraisopropoxytitanate; and the like. Organic tin compounds are preferred, and dioctyltin oxide is more preferred. These silanol condensation catalysts may be used alone or in combination of two or more kinds.
[0073] The content of the silanol condensation catalyst (E) in the curable composition is preferably 1 to 10 parts by mass, more preferably 1 to 5 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the silanol condensation catalyst (E) in the curable composition is 1 part by mass or more, the curing speed of the curable composition can be increased, and the time required for curing the curable composition can be shortened. When the content of the silanol condensation catalyst (E) in the curable composition is 10 parts by mass or less, the curable composition has an appropriate curing speed, and the storage stability and handling of the curable composition can be improved.
[0074] [Plasticizer] The curable composition preferably contains a plasticizer. In the case of a plasticizer other than a polymer or oligomer, a compound having a molecular weight of 300 to 10,000 is used. In the case of a polymer or oligomer, a polymer or oligomer having a number average molecular weight of 400 to 11,000 is used as the plasticizer. Specific examples of the plasticizer include phthalates such as dioctyl phthalate, dibutyl phthalate, and butyl benzyl phthalate, polyalkylene oxides such as polypropylene glycol, and acrylic polymers, and acrylic polymers are preferred.
[0075] The acrylic polymer used as a plasticizer preferably does not contain a hydrolyzable silyl group. The weight average molecular weight of the acrylic polymer used as a plasticizer is preferably 500 to 10,000, more preferably 1,000 to 5,000. When the weight average molecular weight of the acrylic polymer is 500 or more, the bleed-out of the acrylic polymer can be suppressed. When the weight average molecular weight of the acrylic polymer is 10,000 or less, the curable composition is sufficiently plasticized, and the cured product of the curable composition has excellent rubber elasticity.
[0076] The weight average molecular weight of the acrylic polymer used as the plasticizer is a value measured in terms of polystyrene by GPC (gel permeation chromatography). The specific measurement method and conditions are the same as those for the polyalkylene oxide described above.
[0077] The acrylic polymer used as the plasticizer is preferably a polymer obtained by addition polymerization of an acrylic monomer having an ethylenically unsaturated double bond at the ethylenically unsaturated double bond.
[0078] The content of the plasticizer in the curable composition is preferably 100 parts by mass or less, more preferably 90 parts by mass or less, and particularly preferably 1 to 85 parts by mass, relative to 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the plasticizer in the curable composition is 100 parts by mass or less, bleeding out of the plasticizer can be suppressed, and contamination of the cured product of the curable composition can be suppressed.
[0079] [Filler] The curable composition preferably further contains a filler, which makes it possible to provide a curable composition capable of giving a cured product having excellent mechanical strength.
[0080] Examples of the filler include calcium carbonate, magnesium carbonate, calcium oxide, silicic acid hydrate, silicic acid anhydride, finely powdered silica, calcium silicate, titanium dioxide, clay, talc, carbon black, and glass balloons, and calcium carbonate is preferred, and colloidal calcium carbonate and heavy calcium carbonate are preferred. These fillers may be used alone or in combination of two or more.
[0081] The average particle size of calcium carbonate is preferably 0.01 to 5 μm, more preferably 0.05 to 2.5 μm. Calcium carbonate having such an average particle size can provide a cured product having excellent mechanical strength and elongation, and can provide a curable composition having excellent adhesiveness.
[0082] In addition, the calcium carbonate is preferably surface-treated with a fatty acid, a fatty acid ester, etc. Calcium carbonate surface-treated with a fatty acid, a fatty acid ester, etc. can impart thixotropy to the hardenable composition and can inhibit the calcium carbonate from aggregating.
[0083] The content of the filler in the curable composition is preferably 1 to 700 parts by mass, more preferably 10 to 250 parts by mass, and particularly preferably 10 to 200 parts by mass, per 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the filler in the curable composition is 1 part by mass or more, the effect of adding the filler is sufficiently obtained. In addition, when the content of the filler in the curable composition is 700 parts by mass or less, the cured product obtained by curing the curable composition has excellent rubber elasticity.
[0084] [Dehydrating agent] The curable composition preferably further contains a dehydrating agent, which can prevent the curable composition from being cured due to moisture contained in the air or the like during storage of the curable composition.
[0085] Examples of the dehydrating agent include silane compounds such as vinyltrimethoxysilane, dimethyldimethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, phenyltrimethoxysilane, and diphenyldimethoxysilane; and ester compounds such as methyl orthoformate, ethyl orthoformate, methyl orthoacetate, and ethyl orthoacetate. These dehydrating agents may be used alone or in combination of two or more. Among them, vinyltrimethoxysilane is preferred.
[0086] The content of the dehydrating agent in the curable composition is preferably 0.5 to 20 parts by mass, more preferably 1 to 15 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the dehydrating agent in the curable composition is 0.5 parts by mass or more, the effect obtained by the dehydrating agent is sufficiently obtained. In addition, when the content of the dehydrating agent in the curable composition is 20 parts by mass or less, the curable composition has excellent curability.
[0087] [Light stabilizer] The curable composition preferably further contains a light stabilizer, more preferably a hindered amine light stabilizer, which can provide a curable composition that can maintain excellent rubber elasticity for a long period of time after curing.
[0088] Examples of the hindered amine light stabilizer include a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6 poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], and a polycondensate of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol.
[0089] The content of the hindered amine light stabilizer in the curable composition is preferably from 0.01 to 20 parts by mass, and more preferably from 0.1 to 10 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group.
[0090] [Other additives] The curable composition may contain other additives such as a thixotropic agent, an antioxidant, an ultraviolet absorber, a pigment, a dye, an anti-settling agent, and a solvent. Among these, a thixotropic agent, an ultraviolet absorber, and an antioxidant are preferred.
[0091] (Thixotropic agent) The thixotropy-imparting agent may be any agent capable of imparting thixotropy to the curable composition. Preferred examples of the thixotropy-imparting agent include hydrogenated castor oil, fatty acid bisamide, and fumed silica.
[0092] The content of the thixotropy-imparting agent in the curable composition is preferably 0.1 to 200 parts by mass, more preferably 1 to 150 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group. When the content of the thixotropy-imparting agent is 0.1 parts by mass or more, thixotropy can be effectively imparted to the curable composition. When the content of the thixotropy-imparting agent is 200 parts by mass or less, the curable composition has an appropriate viscosity, and the handleability of the curable composition is improved.
[0093] (UV absorber) Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers and benzophenone-based ultraviolet absorbers, and benzotriazole-based ultraviolet absorbers are preferred. The content of the ultraviolet absorber in the curable composition is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group.
[0094] (Antioxidants) Examples of the antioxidant include hindered phenol-based antioxidants, monophenol-based antioxidants, bisphenol-based antioxidants, and polyphenol-based antioxidants, and the like, and the hindered phenol-based antioxidants are preferred. The content of the antioxidant in the curable composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, based on 100 parts by mass of the polyalkylene oxide (A) having a hydrolyzable silyl group.
[0095] The curable composition has excellent adhesive properties and can form a cured product that can maintain excellent rubber elasticity for a long period of time, and therefore can be used in various applications such as a sealant, a coating material, an adhesive, a paint, etc. Among these, it is preferably used as a sealant, and more preferably used as a sealant for joint structure.
[0096] As a method for applying a curable composition to a joint portion to obtain a joint structure, a method is used in which the curable composition is filled into the joint portion and then cured to harden it. The obtained joint structure has a wall member constituting the wall portion of the architectural structure and a hardened product of the curable composition filled into the joint portion formed between adjacent wall members. Examples of the wall portion of the architectural structure include an exterior wall, an interior wall, and a ceiling portion. Examples of the wall member include an exterior wall member, an interior wall member, and a ceiling member.
[0097] The material constituting the wall member is not particularly limited. Examples of wall members include mortar boards, concrete boards, ceramic siding boards, metal siding boards, ALC boards, ceramic boards, and metal boards. Conventional curable compositions have difficulty adhering to wall members such as ceramic boards and cement boards such as lightweight cement boards, but the curable composition of the present invention can exhibit excellent adhesion even to such poorly adhesive wall members. Therefore, poorly adhesive wall members such as ceramic boards and cement boards are preferably used as wall members because they can particularly exhibit the effects of the present invention. The ceramic board is preferably a board made of ceramic. Pottery is a general term for sintered products that utilize the sintering properties of mineral powder. Pottery includes porcelain and earthenware. Porcelain is pottery that has been fired well to the extent that the base has no water absorption. Pottery is pottery that has been fired well to the extent that the base has some water absorption and has been glazed.
[0098] The joints are not particularly limited, and examples thereof include joints in the outer walls, inner walls, and ceilings of architectural structures. The curable composition of the present invention can maintain excellent rubber elasticity for a long period of time after curing, and therefore exhibits excellent followability to changes in the width of the joints due to expansion or contraction of members caused by temperature changes such as air temperature and sunlight, or due to the action of vibration or wind pressure, and can prevent damage to members and water leakage into architectural structures. Therefore, it is suitable for use in sealing joints with large changes in width, also known as "working joints," such as joints in the outer walls of architectural structures. Effect of the Invention
[0099] Since the curable composition of the present invention has the above-mentioned structure, it is capable of exhibiting excellent adhesive properties and maintaining excellent rubber elasticity for a long period of time after curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0100] The present invention will be described in more detail below using examples, but the present invention is not limited thereto. EXAMPLES
[0101] The following raw materials were used in producing the curable compositions of the Examples and Comparative Examples. [Organic polymer (I)] (Polyalkylene oxide (A)) Polyalkylene oxide (A1) (polyalkylene oxide containing methyldimethoxysilyl groups and having a main chain structure of polypropylene oxide, manufactured by AGC Inc., product name "Exestar ES-S4530", number average molecular weight (Mn): 25,000, molecular weight distribution (Mw / Mn): 1.15) Polyalkylene oxide (A2) (polyalkylene oxide containing a methyldimethoxysilyl group and having a main chain skeleton made of polypropylene oxide, manufactured by AGC Inc., product name "SX6735D", number average molecular weight (Mn): 30,000, molecular weight distribution (Mw / Mn): 1.15) Polyalkylene oxide (A3) (polyalkylene oxide containing methyldimethoxysilyl groups and having a main chain structure of polypropylene oxide, manufactured by Kaneka Corporation, product name "Silyl SAX720", number average molecular weight (Mn): 25,000, molecular weight distribution (Mw / Mn): 1.42) Polyalkylene oxide (A4) not containing hydrolyzable silyl groups (AGC Inc., product name "Exestar ES-T2420", number average molecular weight (Mn): 17,000, molecular weight distribution (Mw / Mn): 1.4)
[0102] (Acrylic polymer (B)) An acrylic polymer (B1) whose main chain skeleton is made of a copolymer of methyl methacrylate and n-butyl acrylate (content of methyl methacrylate component: 25% by weight, content of n-butyl acrylate component: 75% by weight) and has a trimethoxysilyl group at the side chain or end of the main chain skeleton, manufactured by Toagosei Co., Ltd., product name "Arphon US-6150", weight average molecular weight: 3,200)
[0103] [Amine compounds (C)] Amine compound (C1) (behenyl propylene diamine, melting point 60°C, NOF Corporation, product name "Nissan Amine DV") Amine compound (C2) (stearylamine, melting point 50°C)
[0104] [Aminosilane compound (D)] Aminosilane compound (D1) (alkoxysilane oligomer which is a hydrolysis condensation product of ethyltriethoxysilane and 3-[N-(2-aminoethyl)amino]propyltriethoxysilane, nitrogen atom content: 6% by mass, liquid state under conditions of 25°C and 0.10 MPa, viscosity (20°C): 20 mPa s, product name "Dynasilan 1146" manufactured by Evonik Degussa Japan) Aminosilane compound (D2) (3-aminopropyltriethoxysilane, liquid at 25°C and 0.10 MPa, viscosity (20°C): 4 mPa·s, product name "KBE-903" manufactured by Shin-Etsu Chemical Co., Ltd.)
[0105] [Silanol condensation catalyst (E)] Silanol Condensation Catalyst (E1) (Dioctyltin Oxide)
[0106] [Plasticizer] Plasticizer (1) (acrylic polymer not containing hydrolyzable silyl groups, weight average molecular weight: 2,000, manufactured by Toagosei Co., Ltd., product name "UP1110")
[0107] [Filler] Colloidal calcium carbonate (Kojima Chemical Co., Ltd. product name "PLS-505", average particle size: 0.1 μm) Heavy calcium carbonate (Shiraishi Calcium Co., Ltd., product name "Whiten SB", average particle size: 2.0 μm)
[0108] [Dehydrating agent] Vinyltrimethoxysilane (product name "KBM-1003" manufactured by Shin-Etsu Chemical Co., Ltd.) [Ultraviolet absorber] Benzotriazole-based UV absorber (BASF Japan product name: Tinuvin 326) [Antioxidants] Hindered phenol antioxidant (BASF Japan product name "Irganox 1010")
[0109] (Examples 1 to 6 and Comparative Examples 1 to 2) The polyalkylene oxide (A1), polyalkylene oxide (A2), polyalkylene oxide (A3), polyalkylene oxide (A4), acrylic polymer (B1), amine compound (C1), amine compound (C2), aminosilane compound (D1), aminosilane compound (D2), silanol condensation catalyst (E1), plasticizer (1), colloidal calcium carbonate, heavy calcium carbonate, vinyltrimethoxysilane, benzotriazole-based ultraviolet absorber, and hindered phenol-based antioxidant were mixed in the amounts shown in Table 1 in a sealed stirrer under reduced pressure until uniform, thereby obtaining a curable composition.
[0110] [evaluation] (Elongation at maximum load: initial) Using the curable composition, an H-shaped specimen was prepared in accordance with JIS A1439 4.21. Specifically, two ceramic plates (thickness 20 mm, length 50 mm x width 50 mm, product name "Super Tri-Wall" manufactured by Tsuruya Co., Ltd.) were used, and a spacer was sandwiched between these ceramic plates to form a rectangular parallelepiped space (length 12 mm x width 50 mm x height 12 mm) in the center between the ceramic plates. The curable composition was filled into this space so that air would not enter. After filling with the curable composition, the curable composition was left for 14 days in an atmosphere with a temperature of 23°C and a relative humidity of 50%. Thereafter, the curable composition was left for another 14 days in an atmosphere with a temperature of 30°C. The curable composition was cured and cured to prepare an H-shaped specimen in which two ceramic plates were bonded and integrated by the cured product of the curable composition.
[0111] Immediately after preparation, the H-shaped specimens were subjected to a tensile test in accordance with JIS A1439 at a tensile speed of 50 mm / min in an atmosphere of 23°C and 50% relative humidity to measure the elongation at maximum load [%]. After the tensile test, the fracture morphology of the cured product of the curable composition was visually confirmed and evaluated according to the following criteria. The results are shown in the "Initial" column in Table 1.
[0112] (Elongation at maximum load: after durability) For durability evaluation, H-shaped specimens were prepared in the same manner as above. Immediately after preparation, the H-shaped specimens were exposed to an atmosphere of 80°C for one month, and then left for an additional 24 hours in an atmosphere of 23°C and 50% relative humidity, and the elongation at maximum load [%] was measured in the same manner as above. Furthermore, after the tensile test, the fracture morphology of the cured product of the curable composition was visually confirmed and evaluated according to the following criteria. The results obtained are shown in the "After durability" column in Table 1.
[0113] The evaluation criteria for the fracture morphology of the cured product of the curable composition were as follows: after the tensile test, if the cured product of the curable composition suffered cohesive failure, it was rated as "CF", and if the cured product of the curable composition suffered interfacial failure, it was rated as "AF".
[0114] The cohesive failure of the cured product means a state where the cured product itself breaks in a tensile test. The interfacial failure of the cured product means a state where the ceramic board and the cured product peel off at the interface in a tensile test. The higher the adhesive strength of the cured product of the curable composition, the more cohesive failure occurs, and the lower the adhesive strength of the cured product of the curable composition, the more interfacial failure occurs.
[0115] [Table 1] [Industrial Applicability]
[0116] The curable composition of the present invention has excellent adhesive properties and can maintain excellent rubber elasticity for a long period of time after curing, and therefore can be suitably used, for example, as a filler for joints formed between exterior wall members that constitute the exterior walls of architectural structures.
Claims
1. A curable composition comprising an organic polymer (I) having a hydrolyzable silyl group, an amine compound (C) having a melting point of 55° C. or higher, an aminosilane compound (D), and a silanol condensation catalyst (E), the organic polymer (I) having a hydrolyzable silyl group comprises 100 parts by mass of a polyalkylene oxide (A) having a hydrolyzable silyl group, and 10 to 200 parts by mass of an acrylic polymer (B) having a hydrolyzable silyl group, The curable composition, wherein the amine compound (C) contains a diamine compound having a melting point of 55° C. or higher.
2. The curable composition according to claim 1, characterized in that the polyalkylene oxide (A) having a hydrolyzable silyl group has a number average molecular weight (Mn) of 20,000 to 50,000 and a molecular weight distribution (Mw / Mn) of 1.3 or less.
3. 3. The curable composition according to claim 1, wherein the aminosilane compound (D) comprises a hydrolysis condensate of an alkoxysilane including an aminoalkoxysilane.
4. 4. The curable composition according to claim 1, wherein the aminosilane compound (D) is a hydrolysis condensate of an alkylalkoxysilane and an aminoalkoxysilane.
5. A wall member constituting a wall portion of an architectural structure; A cured product of the curable composition according to any one of claims 1 to 4, which is filled in a joint formed between the wall members; A joint structure comprising:
Citation Information
Patent Citations
High frequency tempering method of gear
JP1981098422A
Curable composition
JP1994016922A
Curable composition
JP2013060600A
Encapsulation material sheet for solar cell module and method for manufacturing the same
JP2015147899A
Curable composition
JP2018039997A
